La influencia del conflicto social y la licencia social para operar sobre el valor de la empresa - McDonald, Robert (2022)
Based on empirical information from the Peruvian mining sector, a model is proposed that relates social conflict, social license to operate, and the value of extractive companies, in order to contribute to the understanding of socio-entrepreneurial dynamics of the extractive sector. The variables used in the model are the price of mining shares, the official record of conflicts, and social licenses. Using multivariate linear regression, it is found that the increase in social conflicts decreases the value of the companies and that the social license to operate has a positive effect on this variable; moreover, it moderates the impact of the conflict on the value of the company. The study empirically confirms the social and economic relationships between extractive companies and communities, and guides managers, politicians, and authorities to prevent conflicts. It also contributes to closing the gap of empirical studies in less advanced countries.